Statin utilization and cardiovascular outcomes in a real-world primary prevention cohort of older adults - Aaron J. Walker; Jianhui Zhu; Floyd Thoma; Oscar Marroquin; Amber Makani; Martha Gulati; Eugenia Gianos; Salim S. Virani; Fatima Rodriguez; Steven E. Reis; Christie Ballantyne; Suresh Mulukutla; et al. (Elsevier, 2024)
Background: Statins are a cost-effective therapy for prevention of atherosclerotic cardiovascular disease (ASCVD). Guidelines on statins for primary prevention are unclear for older adults (>75 years). Objective: Investigate statin utility in older adults without ASCVD events, by risk stratifying in a large healthcare network. Methods: We included 8,114 older adults, without CAD, PVD or ischemic stroke. Statin utilization based on ACC/AHA 10-year ASCVD risk calculation, was evaluated in intermediate (7.5%-19.9%) and high-risk patients (≥ 20%); and categorized using low and 'moderate or high' intensity statins with a follow up period of ∼7 years. Cox regression models were used to calculate hazard ratios for incident ASCVD and mortality across risk categories stratified by statin utilization. Data was adjusted for competing risk using Elixhauser Comorbidity Index. Results: Compared with those on moderate or high intensity statins, high-risk older patients not on any statin had a significantly increased risk of MI [HR 1.51 (1.17-1.95); p < 0.01], stroke [HR 1.47 (1.14-1.90); p < 0.01] and all-cause mortality [HR 1.37 (1.19-1.58); p < 0.001] in models adjusted for Elixhauser Comorbidity Index. When comparing the no statin group versus the moderate or high intensity statin group in the intermediate risk cohort, although a trend for increased risk was seen, it did not meet statistical significance thresholds for MI, stroke or all-cause mortality. Conclusion: Lack of statin use was associated with increased cardiovascular events and mortality in high-risk older adults. Given the benefits appreciated, statin use may need to be strongly considered for primary ASCVD prevention among high-risk older adults. Future studies will assess the risk-benefit ratio of statin intervention in older adults.